CD64 Staining in Dermatofibroma: A Sensitive Marker Raising the Question of the Cell Differentiation Lineage of This Neoplasm - Mar Llamas-Velasco; Thomas Mentzel; Enrique Ovejero-Merino; María Teresa Fernández-Figueras; Heinz Kutzner (MDPI AG, 2022)
Dermatofibroma (DF) is a mesenchymal tumor of the dermis, but its exact differentiation lineage is still uncertain. A progenitor cell that may be able to differentiate into fibroblastic, myofibroblastic, or fibrohistiocytic cells has been hypothesized. Some authors have also proposed the possibility of a monocytic-histiocytic origin. We stained 47 consecutive dermatofibromas with CD64, CD34, CD14, CD163, and CD68 to test which marker is more reliable for the diagnosis and to gain insight into their histogenesis. From the 35 cases stained with the whole immunohistochemical panel, all were positive for CD64, mostly showing a strong and diffuse pattern. Regarding all the other staining, CD14 was strongly positive in 77% of the lesions and CD163 in 20%. The CD68 stain was intense and diffuse only in 20% of the cases. All lesions were negative for CD34, but two of them showed patchy and weak staining. DFs were immunohistochemically stained positively with a set of macrophage/monocyte/histiocyte lineage markers such as CD14, CD68, CD163, and CD64. This finding favors an active pro-inflammatory immature monocyte-lineage cell as the more suitable origin for DF. CD64 seems to be more sensitive than other markers to confirm the diagnosis.